Top management team expertise and corporate real earnings management activities. (September 2016) - Li, Chihua; Tseng, Yijie; Chen, Tsung-Kang
Abstract: This study investigates the effects of top management team (TMT) expertise on real earnings management (REM) activities by examining a hand-collected data set that contains 4, 690 firm-year observations from Taiwanese listed firms during 2006 to 2010. The results of this study show that the percentages of TMT members possessing master's degrees (PMS) and managing core functional areas (CORE) negatively relate to REM activities, whereas the percentage of TMT members possessing a CPA certificate (PCPA) has the opposite effect. We also find that the PMS and CORE effects are mainly demonstrated through the channel of raising firm performance and thereby reduce managers' incentives to manage earnings. In addition, the effect of TMT expertise on REM activities becomes weaker with increasing firm age. Finally, the outcomes of several robustness tests, such as suspect firm analyses, endogeneity analyses, employing other TMT expertise variables, and additionally controlling for accrual-based earnings management also support our results.